Nanostructure size determination in N+- type porous silicon bY X-Rya diffractometry and Raman Spectroscopy - Ramírez-Porras, A. (Universidad de Costa Rica, 2011)
A series of porous silicon surfaces were obstained after different exposition times of electrochemiscal etching on crystaline n+- type silicon in presence of hydrofluoric acid. These kind of surfaces show photoluminescence when illuminated by UV light. One possible explanation for this is that the treated surface is made up of small crystallites in the nanometer scale that split away the semiconductor band edges up to optical photon energies for the band-to-band recombination processes. In this study, a nanometer size determination of such proposed structures was perfomed by use of X-Ray Diffractometry and Raman Spectroscopy. The results suggest a consistency between the so called Quantum Confined Model and the experimental results.